Prevention of Skin Disorders in Patients with Diabetes Mellitus Using Olive Oil in Semarang City - Suyanto, Suyanto; Muhammad Arifin Noor; Retno Setyawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The high prevalence of diabetes mellitus (DM) leads to serious complications, including dry skin and diabetic foot wounds, which may progress to infection, ulcers, amputation, or even death if not properly managed. Diabetic foot wounds are the most common complications among DM patients, with a prevalence of 75%–90%. To address this issue, a community service program titled